Model analysis for differential pressure two-phase flow rate meter in intermittent flow. (October 2021) - Pellegrini, S.P.; Wrasse, A.N.; da Silva, M.J.; Morales, R.E.M.; Trigo, F.C.; Baliño, J.L.
Abstract: Multiphase flow rate metering is a challenging problem, specially for flow patterns other than wet-gas. This paper brings forward a new comparative analysis of three differential pressure calibration models suited for liquid dominated two-phase flows, in a total of seven model configurations. First, the models are compared theoretically and classified in terms of the type of input data required. Then, experimental data of over 300 horizontal air–water experiments, for 1 " and 2 " pipe diameters, supports quantitative analyses of the prediction accuracies and sensitivity of the superficial velocities of gas and liquid to measurement errors in the model input variables. Finally, a method for assessing the decoupled measurement errors for the void fraction and gas velocity is shown, as these variables are typically subject to higher uncertainties. It results that, though the void fraction is shown to be systematically under evaluated in more than 10%, the total mass flow rate is estimated through the Paz et al. (2010) model with an overall root mean squared deviation (RMSD) of 5.75% for the 2 " data. Also, the use of gas velocity measurements, even if subject to considerable errors, decreased the RMSD for the gas superficial velocity by more than half for the 1 " data. Highlights: Comparison of calibration models for two-phase intermittent flow across restrictions. Analysis of experimental data for Lockhart–Martinelli factor in the range 0 . 67 < χ < 2370 . Best model provides 5.75% root mean squared deviation (RMSD) from reference data. Sensitivity analysis of measurement errors on estimates for superficial velocities. Decoupling of error sources with the support of single-phase reference measurements.